Zawajul asdiqa’ Perkawinan friend - Nasiri Nasiri (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2016)
Marriage friend is a form of marriage muslim teenager without providing shelter and sustenance as requirement, but the couple was still living with a parent , the cost of living still depend on both parents, and they could only meet at any time and agree not to have children first while living apart. In other words, an outline of the purpose of marriage friend is not like the purpose of marriage in Islam, according to the author. The goal is not to establish family relationships and build household, but purely sexual relationship and he belongs to the category of marriage are illegal and should not be done. In addition, the marriage friend could not exist the ideals of marriage itself, namely fostering households sakinah mawaddah wa rahmah. Because a husband doesn’t live together in one house, just stay for a while or live separately, he was just using her for purposes not get a descent so that there is no element of responsibility, and it has been any deviation from God's purpose in marriage ordained. Marriage friend or zawaj al-asdiqa 'is more directed at the fulfillment factor mere sexuality, and bring more harm than maslahat. Marital friend obviously more harm and will bring great fitnah among the people, so that marriage friend are better left for wreaking havoc.